Proyecto de factibilidad para la implementación de una hostería en el zoológico “El Arca” del cantón Archinoda, provincia de Napo - Rosales Santamaría, Jhonathan Lee (2016)
The present research aimed to generate draft a feasibility study for implementation of an inn at the zoo "The Ark" Archidona Canton province of Napo. To develop the work of Analytical Methods, Inductive, Deductive applied, likewise the survey technique was used to the flow of both domestic and foreign tourists who visit the zoo's Ark, taking to the realization of market research sample 318 visitors demand for accommodation establishments and 6 for the offer; which determined the Potential Demand for 1560 visitors, Real Demand 1398 visitors Effective Demand 5124 services, The Offering 2603 and Unmet Demand for 2521 services, In the technical study determined that for the first year of life, the ability installed the inn in 2880 people with a capacity utilization of 80% giving 2,304 people. Also an administrative study determined as a Limited Liability Company, the project reaches an investment of $ 38,904.54 US dollars and will be financed with contributions from partners 49% of the total investment and loan that constitute took place on 51 %. The project has a positive NPV of $ 29,197.49, the IRR of 0.4363%, the recovery time of the original investment would be 1 year, 4 months and 27 days, the benefit cost ratio of 0.35 cents for every dollar spent the project supports a maximum of 7.10% increase in costs and 9.59% decrease in revenue. Among the most significant findings and recommendations have which The market developed in the canton Archidona, determines that the project can and should be run by the results obtained in the analysis of supply and demand. It has been shown that there is considerable unmet demand service. It is recommended to implement this project as it is a good source of income for entrepreneurs.